Identification of Potent and Selective JAK1 Lead Compounds Through Ligand-Based Drug Design Approaches - Babu, Sathya; Nagarajan, Santhosh Kumar; Sathish, Sruthy; Negi, Vir Singh; Sohn, Honglae; Madhavan, Thirumurthy (Frontiers in Pharmacology, 2022)
JAK1 play significant role in the intracellular signalling by interacting with cytokine receptors in different types of cells and linked to the pathogenesis of various cancers and in the pathology of immune system. In this study, ligand-based pharmacophore modeling combined with virtual screening and molecular docking methods were incorporated to identify the potent and selective lead compounds for JAK1. Initially, the ligand-based pharmacophore models were generated using a set of 52 JAK1 inhibitors named C‑2 Methyl/Hydroxyethyl imidazopyrrolopyridines derivatives. 27 pharmacophore models with five and six pharmacophore features were generated and validated using potency and selectivity validation methods. During potency validation, GH score was calculated to check the accuracy of the generated models whereas in selectivity validation the pharmacophore models that are capable of identifying selective JAK1 inhibitors were evaluated. Based on the validation results, the best pharmacophore models ADHRRR, DDHRRR, DDRRR, DPRRR, DHRRR, ADRRR, DDHRR and ADPRR were selected and taken for virtual screening against Maybridge, Asinex, Chemdiv, Enamine, Lifechemicals and Zinc database to identify the new molecules with novel scaffold that can bind to JAK1. 4265 hits were identified from screening and checked for acceptable drug-like properties. 2856 hits were selected after ADME predictions and taken for Glide molecular docking to assess the accurate binding modes of the lead candidates. 90 molecules were shortlisted based on binding energy and H-bond interactions with the important residues of JAK1. The docking results were authenticated by calculating binding free energy for protein ligand complexes using MM-GBSA calculation and induced fit docking methods. Subsequently, cross-docking approach was carried out to recognize the selective JAK1 lead compounds. Finally, top 5 lead compounds which were potent and selective against JAK1 were selected and validated using molecular dynamics simulation. Besides, DFT study was also carried out for the selected leads. Through various computational studies, we observed good potency and selectivity of these lead compounds when compared with the drug ruxolitinib. Compounds such as T5923555 and T5923531 were found to be the best and can be further validated using in vitro and in vivo methods.